(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
The integrated information and communication technology (ICT) as the pedagogical content has led to great opportunities and challenges in the educational ideas and practices. This study explores the contextual use of the ICT integrated pedagogy in Tribhuvan University. The detail analysis has been made on the basis of primary and secondary data collected from the respondents, and literature respectively. The qualitative approach, phenomenological design, constructive paradigm, descriptive methodology and inductive data analysis system have been applied for this study. The ICT technique that teachers apply as a tool or as pedagogy in the classes are analyzed. On the basis of it, the shortcomings, improvements and possible recommendations for the improvement of the existing scenario have been presented.